2008
DOI: 10.2320/matertrans.mra2008150
|View full text |Cite
|
Sign up to set email alerts
|

An Effect of Addition of NiO Powder on Pore Formation in Lotus-Type Porous Nickel

Abstract: Lotus-type porous nickel with cylindrical pores was fabricated by unidirectional solidification in a mixture gas of hydrogen and argon. The pore size is significantly affected by the addition of NiO powder. The pore size decreases and the number density of the pores increases by the addition of NiO. It is concluded that NiO powder can serve as nucleation sites for the pore formation in the process of the solidification.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
3
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 9 publications
1
3
0
Order By: Relevance
“…At present, the nucleation sites of the oxide for formation of pores cannot be observed, because the amount of the oxides is rather small. However, our further research [15] supported the finding that the oxides may serve as the nucleation sites for pore formation. The effect of addition of NiO powder on pore formation in lotus nickel was investigated.…”
Section: Resultssupporting
confidence: 75%
See 1 more Smart Citation
“…At present, the nucleation sites of the oxide for formation of pores cannot be observed, because the amount of the oxides is rather small. However, our further research [15] supported the finding that the oxides may serve as the nucleation sites for pore formation. The effect of addition of NiO powder on pore formation in lotus nickel was investigated.…”
Section: Resultssupporting
confidence: 75%
“…Then, the mold was kept in a closed chamber with constant humidity (90 pct), which was measured by a hydrometer attached to the chamber for a given time, and 0. 15 work can be found in a previous article. [12] The solidification occurs from the bottom of the mold to the top.…”
Section: Introductionmentioning
confidence: 94%
“…There is another factor to contribute the pore size in lotus metals. Recently Onishi et al 11) revealed that intentional addition of fine ceramics powders affects the pore size and the number density of pores in lotus nickel fabricated in hydrogen; the pore size becomes smaller and the number density of pores increases by addition of NiO. NiO may serve as nucleation sites for pore evolution.…”
Section: Resultsmentioning
confidence: 99%
“…Therefore, it is important to find out a method to reduce the pore size without increasing pressure. Recently, Onishi et al [10] reported that addition of NiO powder in molten Ni promoted pore nucleation and led to reduction of pore diameter in lotus Ni fabricated by mold casting technique. This paper concluded that addition of pore nucleation sites in the melt is an effective method to reduce pore diameter.…”
mentioning
confidence: 99%